-(3*5+2)-(-2*5-4)=-3

Simple and best practice solution for -(3*5+2)-(-2*5-4)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3*5+2)-(-2*5-4)=-3 equation:


Simplifying
-1(3 * 5 + 2) + -1(-2 * 5 + -4) = -3

Multiply 3 * 5
-1(15 + 2) + -1(-2 * 5 + -4) = -3

Combine like terms: 15 + 2 = 17
-1(17) + -1(-2 * 5 + -4) = -3

Multiply -1 * 17
-17 + -1(-2 * 5 + -4) = -3

Multiply -2 * 5
-17 + -1(-10 + -4) = -3

Combine like terms: -10 + -4 = -14
-17 + -1(-14) = -3

Multiply -1 * -14
-17 + 14 = -3

Combine like terms: -17 + 14 = -3
-3 = -3

Add '3' to each side of the equation.
-3 + 3 = -3 + 3

Combine like terms: -3 + 3 = 0
0 = -3 + 3

Combine like terms: -3 + 3 = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 10y+5=17 | | 8/(11x-8)=-9x/(11x-8)+2 | | -4(4b+1)+(17b-2)=0 | | 3x+4+5=3 | | -4*-7+7=35 | | 3x^2+6X=-5 | | 16=-2x-6x | | x-4*3=-8 | | X^2-8x+27=0 | | -4=k-3/2 | | x-4*0=-8 | | X^2=182.25 | | X^2-24X=144 | | 9x+5(2x-6)=-9-2x | | 0-4y=-8 | | h=3x1/8+1/4 | | -143-9x=9x+18 | | 4.5q-3.2-4.1q=0.6q-5.2 | | 3m/7=5 | | o=1+6n+5 | | 4+8*-7-3=7*-7+29-3*-7 | | 10y=8x-4 | | -4y+8=-5y+9 | | 9(2*7-3)=3(6*7+5) | | p-36=-46 | | -4/(7y+9)=9/(7y-4) | | 2(x-1)+3=7 | | 8x/3x+2 | | 4x+10=25-2x | | 5/6x+8/9=7/9x | | x-3*3=6 | | 5x+14x=152 |

Equations solver categories